Estimating the value of an early childhood education nutrition program - Mahashabde, Ruchira; Smith, Allen; Massey-Swindle, Taren; Rutledge, Julie M.; Dong, Zhang; Painter, Jacob T. (Frontiers in Nutrition, 2025)
ObjectiveThe objective of the study was to estimate the cost, effectiveness, and value of the Together, We Inspire Smart Eating (WISE) intervention compared to usual nutrition education (UNE) in Arkansas Head Start programs that are part of the Child and Adult Care Food Program (CACFP).MethodsA pre-post study design with non-randomized group assignment was employed to compare cost, body mass index (BMI), and fruit and vegetable intake (measured using the Food Frequency Questionnaire, FFQ) among children aged 3–5 years between September 2015 and April 2018.ResultsChildren at WISE sites showed a greater increase in FFQ scores (0.29 units, p < 0.01) compared to those at UNE sites (0.05 units, p = 0.15), with no significant BMI differences between the groups. The WISE intervention costs $2.16 per child per month, whereas the UNE allocates $3.52 per child per month. Overall, WISE was both more effective and less expensive 25% of the time, costing $0.26 per 1-unit increase in FFQ scores. The WISE intervention remained favorable even when sites were unwilling to pay for its implementation.ConclusionWISE promoted healthier diets at a lower cost than UNE, as evidenced by improved FFQ scores. These findings provide insights for decision makers regarding the intervention’s cost, potential savings, and overall value.